2004
DOI: 10.1373/clinchem.2004.037465
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Measurement of Kynurenine and Tryptophan in Human Plasma and Supernatants of Cultured Human Cells by HPLC with Coulometric Detection

Abstract: host specificity. There thus is little danger that a laboratory worker could be infected (15 ). However, proper clinical laboratory safety precautions should be followed because the phage IACs represent genetically modified organisms. The presented protocol to generate phage IAC could be applied to any clinical PCR assay in which DNA from pathogens is detected. When phage IACs are added to clinical specimens before DNA extraction, all steps of the PCR assay, including lysis of pathogen particles, can be contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 19 publications
0
29
2
Order By: Relevance
“…34 The Kyn/Trp ratio was considered as an index of IDO activity, independent of baseline Trp concentrations. 35 …”
Section: Determination Of Ido Activitymentioning
confidence: 99%
“…34 The Kyn/Trp ratio was considered as an index of IDO activity, independent of baseline Trp concentrations. 35 …”
Section: Determination Of Ido Activitymentioning
confidence: 99%
“…The net consequence of this action is the reduction in TRP concentration in the body. This depletion in turn influences 5-HT production in brain and sends the patient into depression [33][34][35][36][37]. Therefore, TRP depletion is commonly used to recognize the susceptibility of patients towards depression [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…The degradation of tryptophan takes place via two biochemical pathways: biosynthesis of the neurotransmitter serotonin and the kynurenine (Kyn) pathway [5,6]. Trp is the substrate for the first step in both of these pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In the Kyn pathway which is the major catabolic route for Trp, the indole ring of Trp can be opened by the enzymes tryptophan 2,3-dioxygenase (TDO) and indoleamine 2,3-dioxygenase (IDO), yielding N-formylkynurenine which is then converted to Kyn [6][7][8][9][10][11]. The reactions catalyzed by both of these enzymes constitute the rate-limiting step in the Kyn metabolic pathway [2,4,6]. Many studies showed that, like TDO, IDO is also a heme-containing enzyme, despite the fact that it shares no sequence homology with TDO [12].…”
Section: Introductionmentioning
confidence: 99%